Pemberdayaan Ekonomi Umat Berkelanjutan Melalui Program Kampung Zakat di Kampung Oesalaen Kabupaten Kupang Nusa Tenggara Timur - Kamaruddin, Hartono (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This policy paper elaborates on the urgency and effectiveness of the Kampung Zakat program as an effort to empower the community's economy sustainably in Akle Village, Oesalaen Village, East Nusa Tenggara. Through a participatory and local wisdom-based approach, this program targets the education, health, and economic sectors, which serve as the fulcrum for the development of the local community's civilization. This analysis employs the ACTORS theory approach, emphasizing the importance of Authority, Confidence, Trust, Ownership, Resources, and Support in the empowerment process. The writing of this article uses a qualitative method with a descriptive-analytical approach through a case study. Primary data was collected through in-depth interviews with religious leaders, program beneficiaries, and representatives from the National Zakat Board (BAZNAS) of East Nusa Tenggara Province. Meanwhile, secondary data was obtained from documentation studies, Kampung Zakat program reports, and statistical data related to the socio-economic conditions of the Oesalaen Village community. Findings indicate that the success of Kampung Zakat is significantly influenced by the quality of ZIS (Zakat, Infaq, Sadaqah) governance that is oriented towards sustainability and empowerment based on local potential. Therefore, adaptive policy and regulatory strategies, multi-stakeholder support, and the strengthening of zakat literacy are needed so that this program can provide a transformational impact on the long-term welfare of the community.